Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-20T20:22:08+01:00
(0,5xy²-1,2y²+5)+(-0,8y²-2,5xy²-2⅛)=
0,5xy²-1,2y²+5-0.8y²-2.5xy²-2⅛=
-2xy²-2y²+2 ⅞

2. Wykonaj odejmowania:
a) (6a²+2a+1)-(-3a²-2a+5)
6a²+2a+1+3a²+2a-5
9a²+4a-4


b) (12½m²-1¼n²-1,6)-(2¼m²+3¾n²+2,4)
12½m²-1¼n²-1,6-2¼m²-3¾n²-2,4=
25/2m²-5n²-4-9/4m²=
50/4m²-5n²-4-9/4m²=
41/4m²-5n²-4


c) (1,5x²y-¾x²-15)-(⅖x²y-2⅔-⅛x²)
1,5x²y-¾x²-15-⅖x²y+2⅔+1/8x²
15/10x²y-6/8x²-15-4/10x²y+2i2/3+1/8x²
11/10x²y-5/8x²-12i1/3


mam nadzieje ze pomoglam
pozdrawiam.;)



3 5 3
2010-02-20T21:57:33+01:00
1. Usuń nawiasy i wykonaj redukcję wyrazów podobnych:
(0,5xy²-1,2y²+5)+(-0,8y²-2,5xy²-2⅛) =
0,5xy²-1,2y²+5-0,8y²-2,5xy²-2⅛ =
-2xy²-2y²+2⅞

2. Wykonaj odejmowania:
a)
(6a²+2a+1)-(-3a²-2a+5) =
6a²+2a+1+3a²+2a-5 =
9a²+4a-4

b)
(12½m²-1¼n²-1,6)-(2¼m²+3¾n²+2,4) =
12½m²-1¼n²-1,6-2¼m²-3¾n²-2,4 =
10¼m²-5n²-4

c)
(1,5x²y-¾x²-15)-(⅖x²y-2⅔-⅛x²) =
1,5x²y-¾x²-15-⅖x²y+2⅔+⅛x² =
1,1x²y-⅝x²-12⅓